Optimalisasi perkembangan anak usia dini melalui kegiatan bercerita dan membaca nyaring - Aviska, Shella (Maliki Interdisciplinary Journal, 2025)
This article discusses the role of storytelling and read-aloud activities in optimizing early childhood development. Children’s development includes language, cognitive, social, and emotional skills that need to be stimulated from an early age through enjoyable and meaningful learning experiences. Storytelling with simple storybooks can enhance listening skills, enrich vocabulary, and foster an interest in reading. Meanwhile, read-aloud activities allow children to hear expressive language, build self-confidence in speaking, and practice communication skills. Beyond strengthening language, these activities also encourage logical thinking, memory, comprehension, and the ability to connect stories with real-life experiences. Findings show that storytelling and read-aloud practices not only stimulate cognitive growth but also nurture creativity, imagination, and positive attitudes such as confidence and courage. Therefore, integrating storytelling and read-aloud into early childhood education is an effective strategy to support children’s holistic development.